The Influence of the Posner Model on the Conceptual Change of Art Education for the Preparatory Stage (Journal of the College of Basic Education, 2020)
The aim of the research is to diagnose the technical concepts with the wrong understanding of the students of the fourth grade in the four modules of the curriculum of art education to be taught in accordance with the curriculum of the Ministry of Education for the academic year 2018 2019 as well as the impact of the Posner model in the conceptual change of art education for the preparatory stage, The current research in the students of the fourth grade preparatory literature in the middle of Aleppo for boys under the Directorate of Education Wasit / Essaouira for the purpose of application of the experiment, was selected Division (C) simple random drawing method to be the experimental group that will study Art Education B (30) students, while (A) represented the control group that will study the same article in the traditional way (30) students. The researchers were rewarded between the two research groups in a number of variables (the age of students calculated months, diagnostic test " The researchers then tried to control a number of extraneous variables that may affect the dependent variable. After the teaching period, the researchers applied the statistical procedures followed, and when analyzing the results statistically the superiority of the experimental group on the control group was revealed in the results of changing the technical concepts. The researchers concluded that the Posner model proved to be effective in modifying the misconceptions of art education in fourth grade students in the traditional preparatory school, in order to surpass the students of the experimental group that studied the Posner model for students in the control group that studied In the traditional way, the researchers recommended highlighting the importance of constructional theory research applications on which the Posner model is based.